(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
Speaking is defined as the ability to express oneself. Speaking is also referred to as the act of labeling spoken words with the ability to speak hence speaking ability in English is very important. This study aims to identify the correlation between English club membership and speaking ability at Benteng Panynyua English Club (BPEC). However, the results of the analysis showed that there was no significant correlation between membership in the English club and speaking ability. The research method used is quantitative with Pearson’s Product Moment correlation technique. The calculation results show that the level of activeness of members in the English club is 68.8%, while their speaking ability reaches an average value of 75.93. However, the significance coefficient value of 0.364 > 0.05 indicates that there is no significant correlation between the two variables, with a correlation coefficient of -0.253. Thus, it can be concluded that there is no significant relationship between membership in an English club and speaking ability at BPEC.